A minimalist technique for insertion of intrauterine devices - Norman David Goldstuck (PAGEPress Publications, 2015)
The world's population is approaching 7 billion. As a general rule, the countries with the highest population have the least available healthcare resources, the most notable exception being the United States of America (USA). Most of these countries have an urgent need to reduce their populations. The intrauterine device (IUD) is used by the largest number of contraceptives world-wide and it has a proven record in reducing unwanted pregnancies. Its efficacy rate as a long-acting reversible contraceptive is matched only by subdermal implants which are not as cost effective. Although the rates of pelvic infection are elevated in many countries with low-resource health care systems, we now know that pelvic infection rates are independent of IUD usage. This is therefore no longer a contraindication for using IUDs on a large scale in family planning programs. The technique of IUD insertion as described in most textbooks and journals is unnecessarily complex and based on ritual rather than good clinical evidence. This is particularly interesting in that at a time where we prefer evidence based medicine there are still so many clinical practice sacred cows. This article advocates a simplification of the technique for inserting IUDs. The scientific rationale for simplifying the technique is presented, as well as evidence that it is as safe if not safer than the currently suggested methods, if used for the correct type of IUD acceptors.